Sawbones : the horrifying, hilarious road to modern medicine - McElroy, Sydnee; McElroy, Justin, 1980- (Weldon Owen, Inc., 2018)
"Wondering whether eating powdered mummies might be just the thing to cure your ills? Tempted by those vintage ads suggesting you wear radioactive underpants for virility? Ever considered drilling a hole in your head to deal with those pesky headaches? Probably not. But for thousands of years, people have done things like this--and things that make radioactive underpants seem downright sensible! In their hit podcast, Sawbones, Sydnee and Justin McElroy breakdown the weird and wonderful way we got to modern healthcare. And some of the terrifying detours along the way. Every week, Dr. Sydnee McElroy and her husband Justin amaze, amuse, and gross out (depending on the week) hundreds of thousands of avid listeners to their podcast, Sawbones. Consistently rated a top podcast on iTunes, with over 15 million total downloads, this rollicking journey through thousands of years of medical mishaps and miracles is not only hilarious but downright educational. While you may never even consider applying boiled weasel to your forehead (once the height of sophistication when it came to headache cures), you will almost certainly face some questionable medical advice in your everyday life (we're looking at you, raw water!) and be better able to figure out if this is a miracle cure (it's not) or a scam."--